Treatment of primary biliary cholangitis ursodeoxycholic acid non‐responders: A systematic review. (14th June 2017) - Suraweera, Duminda; Rahal, Harman; Jimenez, Melissa; Viramontes, Matthew; Choi, Gina; Saab, Sammy
Abstract: Background: Primary biliary cholangitis (PBC), formerly known as primary biliary cirrhosis, is a chronic cholestatic liver disease characterized by an immune mediated destruction of intrahepatic bile ducts. Ursodeoxycholic acid (UDCA) has been the primary medication for the treatment of PBC, resulting in improved liver tests, resolution of symptoms and increased transplant free survival. However, not all patients respond to UDCA. The aim of this systematic review is to provide an evidence based assessment of the medications that have been studied in patients who are refractory to UDCA. Methods: We performed a systematic literature search on MEDLINE and the Cochrane Database of Systematic Reviews of the published literature. A total of 23 articles fulfilling our inclusion criteria were found. Results: Several studies have shown an improvement in liver biochemistries with the use of obeticholic acid in conjunction with UDCA. Fibrates, including fenofibrate and bezafibrate, have evidence supporting benefit in this population but need more robust studies to confirm these observational results. Neither obeticholic acid nor fibrates have shown to increase transplant free survival. While there may be some benefit with methotrexate, colchicine, budesonide, mycophenolate mofetil and azathioprine, these findings were not consistent and the benefits were marginal. Further investigation is needed. Conclusion: In patients with PBC refractory to UDCA, obeticholic acid or a fibrate is a reasonable choice as an adjunctive treatment to UDCA. Further investigation with randomized controlled trials is needed to provide high quality evidence to formulate standardized therapies in this difficult to treat population.